Removal of microorganisms and antibiotic resistance genes from swine wastewater: a comparison between polyaluminum chloride (PAC), polyaluminum sulfate (LST), and aluminum hydroxide iron (LT). Issue 5 (4th May 2022) - Jian, Yue; He, Yuecheng; Zhu, Jiaming; Long, Dingbiao; Tan, Qiong; Xu, Wenlai; Pu, Shihua
Abstract: The presence of antibiotic-resistant bacteria (ARB) and antibiotic-resistance genes (ARGs) in swine wastewater may present a threat to the environment and public health. Conventional swine wastewater treatment processes generally fail to effectively reduce the content of ARGs. Therefore, it is necessary to develop a highly efficient and low-cost treatment method to solve this environmental problem. In doing so, we evaluated the application of three common coagulants in the treatment of swine wastewater. Using metagenomics, we evaluated the removal efficiency of ARG loads, as well as the effect of coagulation on the structure and diversity of swine wastewater, and on the bacterial community. The results showed that the three coagulants could effectively reduce the physicochemical pollution indexes of swine wastewater (e.g., TP, NTU, COD). After treatment, the loads of a variety of antibiotics in the swine wastewater were significantly reduced, with the exception of NFX and SMD, which were all close to 100%. At the same time, in evaluating the total number of microbial colonies and the total number of fecal Escherichia coli bacteria under the three conditions, Polyaluminum Chloride (PAC) ranked first among the three coagulants with 89.18%, 93.07%, 89.92%, 98.76%, 99.60%, and 98.68%. Metagenomic analysis revealed that the abundance of cfcC, tetX, mphE, msrE, tet36, and other ARGs in the water sample after the LST treatment was significantly lower than that of the original swine wastewater sample. These findings demonstrate the feasibility of using coagulants to treat swine wastewater, which is of great significance for improving water quality and reducing the potential impacts of ARGs.